Paediatric diabetes subtypes in a consanguineous population: a single-centre cohort study from Kurdistan, Iraq - Amaratunga, Shenali A; Hussein Tayeb, Tara; Muhamad Sediq, Rozhan N; Hama Salih, Fareda K; Dusatkova, Petra; Wakeling, Matthew N; De Franco, Elisa; Pruhova, Stepanka; Lebl, Jan (Diabetologia, 2024)
AIMS/HYPOTHESIS: Monogenic diabetes is estimated to account for 1-6% of paediatric diabetes cases in primarily non-consanguineous populations, while the incidence and genetic spectrum in consanguineous regions are insufficiently defined. In this single-centre study we aimed to evaluate diabetes subtypes, obtain the consanguinity rate and study the genetic background of individuals with syndromic and neonatal diabetes in a population with a high rate of consanguinity. METHODS: Data collection was carried out cross-sectionally in November 2021 at the paediatric diabetic clinic, Dr Jamal Ahmad Rashed Hospital, in Sulaimani, Kurdistan, Iraq. At the time of data collection, 754 individuals with diabetes (381 boys) aged up to 16 years were registered. Relevant participant data was obtained from patient files. Consanguinity status was known in 735 (97.5%) participants. Furthermore, 12 families of children with neonatal diabetes and seven families of children with syndromic diabetes consented to genetic testing by next-generation sequencing. Prioritised variants were evaluated using the American College of Medical Genetics and Genomics guidelines and confirmed by Sanger sequencing. RESULTS: A total of 269 of 735 participants (36.5%) with known consanguinity status were offspring of consanguineous families. An overwhelming majority of participants (714/754, 94.7%) had clinically defined type 1 diabetes (35% of them were born to consanguineous parents), whereas only eight (1.1%) had type 2 diabetes (38% consanguineous). Fourteen (1.9%) had neonatal diabetes (50% consanguineous), seven (0.9%) had syndromic diabetes (100% consanguineous) and 11 (1.5%) had clinically defined MODY (18% consanguineous). We found that consanguinity was significantly associated with syndromic diabetes (p=0.0023) but not with any other diabetes subtype. The genetic cause was elucidated in ten of 12 participants with neonatal diabetes who consented to genetic testing (homozygous variants in GLIS3 [sibling pair], PTF1A and ZNF808 and heterozygous variants in ABCC8 and INS) and four of seven participants with syndromic diabetes (homozygous variants in INSR, SLC29A3 and WFS1 [sibling pair]). In addition, a participant referred as syndromic diabetes was diagnosed with mucolipidosis gamma and probably has type 2 diabetes. CONCLUSIONS/INTERPRETATION: This unique single-centre study confirms that, even in a highly consanguineous population, clinically defined type 1 diabetes is the prevailing paediatric diabetes subtype. Furthermore, a pathogenic cause of monogenic diabetes was identified in 83% of tested participants with neonatal diabetes and 57% of participants with syndromic diabetes, with most variants being homozygous. Causative genes in our consanguineous participants were markedly different from genes reported from non-consanguineous populations and also from those reported in other consanguineous populations. To correctly diagnose syndromic diabetes in consanguineous populations, it may be necessary to re-evaluate diagnostic criteria and include additional phenotypic features such as short stature and hepatosplenomegaly.
Keywords: senioři; Consanguinity; Syndromic diabetes; pokrevní příbuzenství; Infant, Newborn, Diseases; Genetics; diabetes mellitus 1. typu; Cohort Studies; Iraq; mužské pohlaví; Diabetes Mellitus, Type 2; Consanguineous population; mutace; diabetes mellitus 2. typu; Monogenic diabetes; kohortové studie; dítě; Child; Irák; Paediatric diabetes; Infant, Newborn; Diabetes Mellitus, Type 1; novorozenec; Mutation; Humans; Diabetes genes; Neonatal diabetes; nemoci novorozenců; proteiny přenášející nukleosidy; Nucleoside Transport Proteins; Aged; lidé; Male